2007
DOI: 10.2967/jnumed.107.043430
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Gene Expression in Live Pancreatic Islet Cell Lines Using Dual-Isotope SPECT

Abstract: We are combining nuclear medicine with molecular biology to establish a sensitive, quantitative, and tomographic method with which to detect gene expression in pancreatic islet cells in vivo. Dual-isotope SPECT can be used to image multiple molecular events simultaneously, and coregistration of SPECT and CT images enables visualization of reporter gene expression in the correct anatomic context. We have engineered pancreatic islet cell lines for imaging with SPECT/CT after transplantation under the kidney caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…We have previously used the HSV1-tk reporter gene to image transplanted pancreatic islet cells in vivo [2]. A number of studies have now shown that islet transplants can be monitored over time using islets transfected with adenoviral or lentiviral sr39tk constructs and [ 18 F]FHBG as a PET probe [3][4][5].…”
mentioning
confidence: 99%
“…We have previously used the HSV1-tk reporter gene to image transplanted pancreatic islet cells in vivo [2]. A number of studies have now shown that islet transplants can be monitored over time using islets transfected with adenoviral or lentiviral sr39tk constructs and [ 18 F]FHBG as a PET probe [3][4][5].…”
mentioning
confidence: 99%
“…43,50,55,70,[78][79][80][83][84][99][100][101][171][172][173][174][175][176][177][178][179] To image cell location, survival and proliferation and determine the cell's quantity at a certain site, cells are first genetically engineered in culture to express RGs under the control of a strong constitutive promoter (i.e., ubiquitin). Then, after the genetically modified cells are adoptively transferred, the recipient is scanned with the imaging modality instrumentation needed to image the expression of the RG that is inserted into the cells (Fig.…”
Section: Pet/spect Reporter Gene Imaging In Cell Therapy and Organ Trmentioning
confidence: 99%
“…[13][14][16][17][18][19][20][22][23][24][25][26][27][32][33][34][35][36][37][38][39] These probes take advantage of the fact that HSV1-TK and its mutants, especially HSV1-sr39TK, have a much higher affinity for them than the cytoplasmic mammalian TKs. Amongst acycloguanosine probes, 9-(4- 18 [4][5]11,27,[34][35][36]72,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] Regardless of sensitivity, the use of each probe has its advantages and disadvantages. For example, [ 18 F]FEAU is predominantly cleared through the renal pathways, hence its low gastrointestinal signal make it a better probe for imaging in the lower abdomen.…”
Section: Herpes Simplex Virus 1 Thymidine Kinase and Its Mutant Derivmentioning
confidence: 99%
“…It is typically advantageous to combine such a micro-SPECT system with micro-CT, in order to provide highresolution coregistered images of anatomy (Ritman, 2002;Tai et al, 2008). Figure 15 illustrates the capability to perform coregistered cardiac imaging with micro-SPECT and micro-CT in a mouse with the U-SPECT-II/CT system (MILabs, Utrecht, the Netherlands).…”
Section: Attenuation Correction In Emission Tomographymentioning
confidence: 99%